State of the art of university social responsibility: a standardized model and compared self-diagnosis in Latin America. Issue 3 (7th March 2022) - Vallaeys, François; Oliveira, M.L.S.; Crissien, Tito; Solano, David; Suarez, Andres
Abstract : Purpose: This paper aims to provide information about the state of the art of University Social Responsibility (USR) from a regional perspective, based on a theoretical and practical development proposed by a wide net of Latin-American higher education institutions (HEIs): the USR Union of Latin America (URSULA). Design/methodology/approach: The state of the art was performed through a two-year measurement process (2018–2019) conducted in 80 HEI from 12 Latin-American countries. The state of the art was constructed through a self-reported diagnosis concerning four HEI scopes of action, twelve goals, and sixty-six indicators to measure the accomplishment of USR goals. Findings: The study's primary results were twofold: first, the verification of a dynamic model for USR consensual management and second, the understanding of USR's challenging nature for standard practices in HEIs. Practical implications: This study's results contribute to creating a practical framework for USR measurement based on a regional context (Latin America). Moreover, this research underlines the discrepancy between HEIs' social performance and the need to commit to the 2030 UN sustainable development goals. Originality/value: This is the first study to examine the state of USR in a region such a Latin America.